2012
DOI: 10.1089/ees.2011.0237
|View full text |Cite
|
Sign up to set email alerts
|

Percarbonate as a Hydrogen Peroxide Carrier in Soil Remediation Processes

Abstract: Use of sodium percarbonate (SPC) as a hydrogen peroxide (H 2 O 2 ) carrier in polycyclic aromatic hydrocarbon (PAH)-contaminated soil remediation has been assessed. A series of SPC decomposition runs in PAH-free soil were conducted in the presence of different soil amounts and temperatures. Results suggest the development of first-order H 2 O 2 decomposition kinetics. Soil mass exerts a positive effect in terms of H 2 O 2 abatement rate. An order of 2/3 in H 2 O 2 decomposition was calculated regarding soil do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 11 publications
(7 reference statements)
0
8
0
4
Order By: Relevance
“…Recent studies have shown that peroxymonocarbonate ion (HCO 4 À , E 0 = 1.8 V vs. SHE) can be generated through the equilibrium between HCO 3 À and H 2 O 2 in aqueous solution, as shown in Eq. (11), and other active species are further generated by the decomposition of HCO 4 À [27]. HCO 4 À itself can be a potent oxidant and be capable of oxidizing a variety of organic compounds [27].…”
Section: Ion Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that peroxymonocarbonate ion (HCO 4 À , E 0 = 1.8 V vs. SHE) can be generated through the equilibrium between HCO 3 À and H 2 O 2 in aqueous solution, as shown in Eq. (11), and other active species are further generated by the decomposition of HCO 4 À [27]. HCO 4 À itself can be a potent oxidant and be capable of oxidizing a variety of organic compounds [27].…”
Section: Ion Effectmentioning
confidence: 99%
“…Sodium percarbonate (2Na 2 CO 3 Á3H 2 O 2 , SPC), as an adduct of 32.5% hydrogen peroxide and 67.5% sodium carbonate (based on weight) [10], has recently been used as another oxidant for ISCO [11]. Compared with liquid H 2 O 2 , SPC comes in a solid form that can be used as a dry carrier of H 2 O 2 and as a granulated powder is easier to transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in contrast to peroxide, a major advantage of using SPC for ISCO application is that it is effective over a relatively wide range of pHs [13, 14]. In addition, the SPC decomposition products are non-toxic to micro-organisms owing to its compatibility with bioremediation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies were conducted by applying Fenton-like processes. To the best of our knowledge, few studies to date have investigated Fe(III) catalyzed SPC oxidation of chlorinated-solvent compounds [22]. And the issue of Fe(III) stability in catalyzed SPC system has not been addressed.…”
Section: Introductionmentioning
confidence: 99%